Adult Education and Development, 1993 - German Adult Education Association, Bonn (Germany). Inst. for International Cooperation; Hinzen, Heribert; German Adult Education Association, Bonn (Germany). Inst. for International Cooperation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
These two issues of a half-yearly journal for adult education cover Africa, Asia, and Latin America. Number 40 consists of 35 articles on 4 themes: Multicultural dimensions; environmental learning; cooperation and partnership with Eastern Europe; and women and training. Articles include: "It Is Time to Understand that the World Belongs to All of Us" (Mane); "The Bensheimer Kreis Demands: Give Priority to Fighting the Causes for Large Refugee Movement!"; "Western Man--A Master of Detail But Blind to the Whole" (Willamo); "A Critical View of Environmental Education" (von Sanden, Evia); "Polish and German Coexistence" (Samlowski); "Adult Education in the Process of Rebuilding the Economy" (Marcinkiewicz); and "Systematizing Gender-Based Interventions: The Mindanao Experience" (Polestico). Number 41 consists of 22 articles on 3 major themes: indigenous peoples and learning; development and community participation; and adult education and training. Articles include: "What Is a True Indigenous School?: Indigenous Societies of Brazil and Their Schools" (Grupioni, Ferreira); "Literacy, Language, and the International Year for the World's Indigenous Peoples" (Brennan); "The Idiofa Peasant's Participation in Rural Development--A Lawsuit against the State" (Lowola); "To Collaborate in Order To Promote Laws in Rural Areas and Fight against Injustices"; (Mulunda, Ntashushwa); "What Brings about Changes in the Local Community" (Koineh); "Eradication of Illiteracy of Women and Girls in Vietnam" (Van); and "Expanding Training Delivery for Job Generation" (Gamerdinger). (YLB)
Availability: Institute for International Cooperation, German Adult Education Association, Obere Wilhelmstrasse 32, D-53225 Bonn, Germany.
ERIC Note: Photographs may not copy adequately. For related document, see CE 066 244.
Adult Education and Development, n40-41 1993.
Microfiche.
Keywords: Adult Education; Case Studies; Correctional Education; Cultural Pluralism; Developing Nations; Economic Development; Educational Development; Environmental Education; Ethnic Groups; Foreign Countries; International Cooperation; Multicultural Education; Womens Education; Africa -- Asia -- Bulgaria -- Colombia -- Germany -- Great Britain -- Hungary -- Latin America -- Namibia -- Nigeria -- Papua New Guinea -- Poland -- Russia -- Rwanda; Collected Works, Serials